Merger and Centralisation : can We be Big AND Good - Simpson, Bill (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
The merger of the Victoria University of Manchester and UMIST in 2004 to create Britain’s largest university (though the achievement of world-class status rather than mere size was the real objective of the merger) raised a range of parallel issues for the libraries of the two universities and for the Manchester Business School (MBS) Library, which had previously operated independently, but was also merged into the new University Library. The first issue was the name of the new library and here the shift was so subtle that few people notice it until it is pointed out to them. If the “John Rylands University Library, The University of Manchester” seems hardly to differ from the “John Rylands University Library of Manchester” (the name of the former Victoria University of Manchester’s Library), this is because the Rylands name already has global brand recognition and it would have been foolish to risk a major name change that might have put that recognition at risk. It was a case of subtly shifting the emphasis of the name to reflect the fact that we are a new entity whilst not creating confusion in relation to our great historic collections.